2016
DOI: 10.3390/condmat1010008
|View full text |Cite
|
Sign up to set email alerts
|

Silicene Nanoribbons on Pb-Reconstructed Si(111) Surface

Abstract: We report on the initial stage of growing of silicon nanostructures on Pb-induced √ 3 × √ 3 and √ 3 × √ 7 reconstructed Si(111) surfaces. The deposition of 0.75 monolayer of Si at a temperature of around 200 K results in Si nanoribbons a few-nanometers in length running in three equivalent high symmetry directions of Si(111) surface, as revealed by low temperature scanning tunneling microscopy measurements. The nanoribbons are predominantly 1.6 nm wide and show local √ 3 × √ 3 reconstruction. These findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 70 publications
6
11
0
Order By: Relevance
“…1 shows an example of such NRs as revealed by STM topography measurements. The NRs consist of Si atoms directly adsorbed on the Si(111) surface, as it was argued in [ 47 ], based on geometry considerations and STM measurements. It is also known, that Pb atoms strongly diffuse on Si substrates [ 53 54 ], so they can easily make room for growing Si NRs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 shows an example of such NRs as revealed by STM topography measurements. The NRs consist of Si atoms directly adsorbed on the Si(111) surface, as it was argued in [ 47 ], based on geometry considerations and STM measurements. It is also known, that Pb atoms strongly diffuse on Si substrates [ 53 54 ], so they can easily make room for growing Si NRs.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the Si layer was deposited onto the sample held at 200 K within 20 min. Details of the preparation can be found in [ 47 ]. The presented nanoribbons were obtained by two-step annealing: first at room temperature for 1 h, and then by direct heating at around 400 K for 5 min.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that in the case of homoepitaxy of GaAs, the Pb layer acts as a surface agent, enhancing layer-by-layer growth . A similar effect was observed on the Cu and Si(111) surfaces. , All of these studies, experimental as well as theoretical, were devoted to epitaxial growth on flat low-index surfaces.…”
Section: Introductionmentioning
confidence: 85%